How much are "many people" on facebook?: Interpretations of vague quantifiers in online and offline contexts - Moll, Ricarda; Lücke, Anna J.; Bromme, Rainer (Sage open, 2021)
In an increasingly interconnected world, many people handle large parts of their communication online, often via social networking sites (SNS). In contrast to face-to-face communication, messages on SNS are accessible by potentially unknown and large audiences. However, it is an open question what users actually perceive as a large audience, or else as many people in SNS contexts. Exploring this question from a psycholinguistic perspective, we investigated the meaning of vague quantifiers such as "few" or "many" with regard to audiences in different contexts in two experiments. In Experiment 1, participants assigned numbers to quantifiers describing audiences in online versus offline and private versus public contexts. In Experiment 2, including the same items as Experiment 1, participants rated the appropriateness of specific numbers of people that were described by a quantifier. Our results show, for example, that people assigned larger numbers to quantifiers for online than for offline contexts. This was also true when access to the information was supposed to be restricted which implies a (scalar) change of privacy expectations.
Gesehen am 07.10.2021